2014
DOI: 10.1103/physrevb.89.121407
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of a line defect in graphene and implications for gate-tunable valley filtering

Abstract: Atomically precise tailoring of graphene can enable unusual transport pathways and new nanometer-scale functional devices. Here we describe a recipe for the controlled production of highly regular "5-5-8" line defects in graphene by means of simultaneous electron irradiation and Joule heating by applied electric current. High-resolution transmission electron microscopy reveals individual steps of the growth process. Extending earlier theoretical work suggesting valley-discriminating capabilities of a graphene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 32 publications
8
103
0
Order By: Relevance
“…We do not rule out the possibility that sublimation/condensation may play some role in the structural transformation, but suggest that it is probably not the major factor. We note that recent in situ Joule heating experiments have shown that carbon sublimation can result in the formation of certain line defects in graphene [18].…”
Section: Discussionmentioning
confidence: 71%
“…We do not rule out the possibility that sublimation/condensation may play some role in the structural transformation, but suggest that it is probably not the major factor. We note that recent in situ Joule heating experiments have shown that carbon sublimation can result in the formation of certain line defects in graphene [18].…”
Section: Discussionmentioning
confidence: 71%
“…Though it is not straightforward to realize this system, because line defects have to be created in a controlled fashion and then have to be decorated with the transition metal, the situation does not look hopeless. Pristine line defects have been observed in as-grown graphene [5] and can also be induced by electron irradiation [6,7]. In addition, substantial preferential bonding of the Mn atoms at octagonal hollow sites overcomes the problem that transition-metal atoms usually are very mobile on graphene.…”
Section: Discussionmentioning
confidence: 93%
“…This defect with fractional chirality was predicted previously for nanotubes [4] and, referring to the arrangement of the rings, is called 8-5-5-8 topological line defect. It has been observed in as-grown graphene [5] and can also be induced in a controlled fashion by electron irradiation [6,7]. In general, the intentional introduction of defects into graphene is a topic that currently receives enormous attention, because it can lead to a multitude of applications [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…1f) can be viewed as a degenerate GB as it has zero misorientation angle. Because of its topologically trivial structure, this defect can be engineered in a controlled way, as demonstrated by Chen et al 46 . Another work observed a different line defect in graphene oriented along the armchair direction 47 .…”
Section: Structure Of Polycrystalline Graphenementioning
confidence: 99%